2014
DOI: 10.1039/c4sm01528b
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic interactions of ionic liquids with lipid biomembranes: a molecular simulation study

Abstract: Current bottlenecks in the large-scale commercial use of many ionic liquids (ILs) include their high costs, low biodegradability, and often unknown toxicities. As a proactive effort to better understand the molecular mechanisms of ionic liquid toxicities, the work herein presents a comprehensive molecular simulation study on the interactions of 1-n-alkyl-3-methylimidazolium-based ILs with a phosphatidylcholine (PC) lipid bilayer. We explore the effects of increasing alkyl chain length (n = 4, 8, and 12) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
136
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(160 citation statements)
references
References 83 publications
20
136
1
3
Order By: Relevance
“…The lipophilic alkyl chain of the IL penetrates into the hydrophobic region of the lipid bilayer making it rough. This can induce disruption and leakage of the lipid bilayer and eventually cell death [12][13][14][15]. However, short chained amidium and imidazolium ILs showed no significant cytotoxicity under the tested conditions.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The lipophilic alkyl chain of the IL penetrates into the hydrophobic region of the lipid bilayer making it rough. This can induce disruption and leakage of the lipid bilayer and eventually cell death [12][13][14][15]. However, short chained amidium and imidazolium ILs showed no significant cytotoxicity under the tested conditions.…”
Section: Introductionmentioning
confidence: 80%
“…They noticed that the alkyl chains of the tested ILs were deeply inserted into the hydrophobic region of the phospholipid bilayers and the penetration was dependent on the alkyl chain length. The penetration of the ILs increased the lateral movement of the lipids and moreover, with increasing IL concentrations the surface became rough, which could be a precursor for bilayer disruption [14].…”
Section: Effect Of Ionic Liquids On Analyte-liposome Interactionsmentioning
confidence: 99%
“…Further investigations into the connection between cytotoxicity, cation chain length, and RTIL concentration have been done by Maginn and co-workers by combining several experimental techniques with computer simulations (Yoo et al 2014(Yoo et al , 2016a. Their main result was the concentration-dependence study of RTILs on biomembranes.…”
Section: Introductionmentioning
confidence: 99%
“…This article is part of a Special Issue on 'IUPAB Edinburgh Congress' edited by Damien Hall (v) Penetrate, create pores, and destroy biomembranes (Benedetto et al 2014b, Bhattacharya et al 2017, Evans 2008, Yoo et al 2014, b, Wang et al 2015a, b, 2016Drücker et al 2017; and (vi) Dissolve cellulose and other complex polysaccharides (Youngs et al 2011, Zhang et al 2017, Cheng et al 2011, Liu et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…47 The anions moiety of the ILs on the other hand have also been reported to get inserted in the lipid bilayer. 48 The morphological effects of such phenomenon is the alteration in cell membrane permeability as well as its cellular functions. 19 In a similar study, ILs have been shown to disrupt the ion channels in the membrane thereby disturbing the homeostasis.…”
Section: Viability Studies By Mtt Assay In the Presence Of Compatiblementioning
confidence: 99%